Galactic dynamics feeding the Galactic center. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Renaud, Florent; Emsellem, Eric; Bournaud, Frédéric
Abstract: We present the hierarchical structure of the gas and its rapid evolution in the central region of a simulation of the entire Milky Way, run at subparsec resolution. We emphasize the coupling between the kpc-scale dynamics, the molecular ring and the central 5 pc disk feeding the supermassive black hole.